Transformasi Sumber Daya Manusia Pialang Asuransi Indonesia: Isu Kompetensi, Digitalisasi, dan Kepatuhan - Sasongko, Angky Budi; Sitti Rakhman (Jurnal Deliberatif, 2025)
This study explores the transformation and strategic challenges of human resources (HR) in non-life insurance brokerage and reinsurance companies in Indonesia, considering the digital era and current OJK regulations. The main issues identified include competency gaps among personnel, the low proportion of certified staff, and stagnating broker contributions to national premium distribution. The digitalization of business processes, the need to strengthen agile leadership, and increasing compliance pressure—especially with OJK Regulation Number 34 of 2024 regarding HR development investment—intensify the adaptation processes within organizations. A qualitative-descriptive approach was employed, combining literature review and secondary data analysis (OJK, AAUI, and BPS statistics 2022–2025), as well as benchmarking with international best practices and empirical studies. The results show that digital competency, adaptive HR governance, and synergistic ongoing training programs are pivotal drivers of HR transformation in local brokers towards global standards. Strategic recommendations encompass digital-based recruitment redesign, the implementation of compliance-driven HR audits, agile work culture development, and cross-association and global partnership collaboration. This study concludes that agility, digital literacy, and robust HR governance are the keys to ensuring the competitiveness and sustainability of Indonesian brokerage and reinsurance companies in regional and global insurance markets.